2004
DOI: 10.1152/ajpheart.01050.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A-mediated cross-talk between p38 MAPK and ERK in apoptosis of cardiac myocytes

Abstract: Mitogen-activated protein kinases (MAPKs) play different regulatory roles in signaling oxidative stress-induced apoptosis in cardiac ventricular myocytes. The regulation and functional role of cross-talk between p38 MAPK and extracellular signal-regulated kinase (ERK) pathways were investigated in cardiac ventricular myocytes in the present study. We demonstrated that inhibition of p38 MAPK with SB-203580 and SB-239063 enhanced H(2)O(2)-stimulated ERK phosphorylation, whereas preactivation of p38 MAPK with sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
118
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 42 publications
13
118
1
9
Order By: Relevance
“…11,[27][28][29][30][31][32] We observed a strong significant positive association between the activation status of cytoplasmic JNK, p38, and ERK1/2 in superficial spreading melanomas as well as an association between activation of Akt and p38 in the cytoplasm. In a study by Pedram et al 32 expression of vascular endothelial growth factor was shown to induce a positive ERK1/2-JNK crosstalk in endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11,[27][28][29][30][31][32] We observed a strong significant positive association between the activation status of cytoplasmic JNK, p38, and ERK1/2 in superficial spreading melanomas as well as an association between activation of Akt and p38 in the cytoplasm. In a study by Pedram et al 32 expression of vascular endothelial growth factor was shown to induce a positive ERK1/2-JNK crosstalk in endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, our data are not in agreement with studies showing a negative cross-talk mechanism between p38 and ERK1/2 in several tissues. 11,[27][28][29] Common for these studies is the observation that inhibiting one pathway induces a robust increase in activation of the other and vice versa. This again demonstrates the complexity of signaling in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Syntaxin 1A has been shown to be phosphorylated by different protein kinases, and phosphorylation of syntaxin 1A regulates its interaction with other proteins (Foletti et al, 2000;Tian et al, 2003). p38 MAPK regulates the activity and translocation of PP2Ac (Liu and Hofmann, 2004). Thus, phosphatase activity from the SERT-P2Ac complex may participate at different levels, maintaining appropriate levels of functional SERTs to coordinate with various cellular stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…62 Moreover, PP2A mediates a cross talk between p38 MAPK and ERK in cardiac myocytes, as shown by increased ERK phosphorylation in H 2 O 2 -stimulated ventricular myocytes in response to okadaic acid. 60 Based on these observations, it can be imagined that p38 MAPK might regulate HQ-induced ERK activation through PP2A in ARPE-19 cells. Future studies will test this hypothesis.…”
Section: Hsp27 and Oxidative Stress In Rpe 1211mentioning
confidence: 99%
“…63 One-way cross talk between p38 and ERK has been reported in various cells. 60,64,65 To further investigate the relationship between p38 and ERK pathways in response to HQ in ARPE-19 cells, we examined the effects of MEK inhibitor PD98059 on HQ-induced phosphorylation of p38. We found that PD98059 decreased HQ-induced p38 MAPK activation indicating that ERK1/2 pathway positively modulates p38 signaling and that ERK is required for HQ-induced activation of p38 MAPK signaling pathway in human RPE cells.…”
Section: Hsp27 and Oxidative Stress In Rpe 1211mentioning
confidence: 99%